2020
DOI: 10.1080/13533312.2020.1753513
|View full text |Cite
|
Sign up to set email alerts
|

All the World’s a Stage, and Sanctions the Merely Props: an Interactional Account of Sender-Target Dynamics in the Ukrainian Crisis

Abstract: This article argues that sanctions are interactional tools; their interactive nature is evident if these measures are considered as a form of stigmatization, which is the outcome of an interaction between the group imposing the stigma and the actor that is stigmatized. Stigmatized states do not always accept the label that is placed upon them and can adopt strategies to counter or resist stigma. From a symbolic interactionalist perspective, this can be understood as a state's foreign policy role. Such an appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In punishing Russia, the West denies its status and refuses to it treat as an equal. Concerned with its status, Russia rejects the role of the deviant and presents itself as an 'untouchable' state that cannot be influenced by foreign powers (discussed further Hofer, 2020). The Kremlin has adapted to the sanctions by adopting a strategy that lies between 'stigma rejection' and 'counter-stigma' and that mirrors the actions of a resentful action as described by Wolf.…”
Section: Two Illustrations: Russia and Venezuela's Management Of Sanctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In punishing Russia, the West denies its status and refuses to it treat as an equal. Concerned with its status, Russia rejects the role of the deviant and presents itself as an 'untouchable' state that cannot be influenced by foreign powers (discussed further Hofer, 2020). The Kremlin has adapted to the sanctions by adopting a strategy that lies between 'stigma rejection' and 'counter-stigma' and that mirrors the actions of a resentful action as described by Wolf.…”
Section: Two Illustrations: Russia and Venezuela's Management Of Sanctionsmentioning
confidence: 99%
“…Adopting a symbolic interactionist approach (McCourt, 2012;Smetana, 2019;Hofer, 2020), the present article seeks to understand what motivates this contestation, thereby providing further insight on how unilateral sanctions influence inter-state relations. It is suggested that sanctions' punitive nature, implying a hierarchy between the sender and the target, is what triggers contestation against these practices.…”
mentioning
confidence: 99%